Research methods and data analysis techniques in education articles published by Indonesian biology educational journals - Ahmad Fauzi; Ika Wahyu Pradipta (University of Muhammadiyah Malang, 2018)
The essential of studies which focus on research methods in biology educational field is providing recommendations for the next researchers the proper methods they need to use. Unfortunately, this kind of research is still hard to find in Indonesia. The aim of this study was to access the diversity of research approaches, designs, variables, data collection and analysis techniques, as well as research subjects in the articles published in Indonesian biology educational journals throughout 2017. Content analysis was used as the research design in this study in which as many as 122 articles were analyzed. The results revealed that the most type, design, variable, data collection and analysis techniques, as well as the subject which frequently used were R&D, Quasi-experimental, media/learning sources, questionnaire, frequency and percentage, and senior high school respectively. There were variety of approaches, designs, data collection and analysis techniques, as considerable as research subjects which have been used in educational research. Moreover, there also findings that some several studies with the same research design applied different data collection and data analysis techniques. Thus, it is suggested to the next researchers to choose the most proper methods in conducting their researches.